Complexes of Oligoribonucleotides with D-Mannitol Inhibit Hemagglutinin-Glycan Interaction and Suppress Influenza A Virus H1N1 (A/FM/1/47) Infectivity In Vitro - Nataliia Melnichuk; Larisa Semernikova; Zenoviy Tkachuk (MDPI AG, 2017)
The influenza virus hemagglutinin (HA) mediates both receptor (glycan) binding and membrane fusion for cell entry and has been the basis for subtyping influenza viruses. The oligoribonucleotides-d-mannitol (ORNs-d-M) complexes possess an anti-influenza activity in vitro and in vivo. In the present studies, we have found that ORNs-d-M interferes with hemagglutinin (HA)-glycan interaction and suppress viral infection in host cells. HA-glycan interactions were evaluated to indirectly quantify the amount of influenza virus titer by an agglutination assay. Influenza virus infectivity was determined by TCID50 assay. The direct virucidal action of the complexes was evaluated by both cytopathic effects (CPE) reduction assay and cell MTT assay. We found that ORNs-d-M hinders interaction between HA and glycan. These complexes decreased the infectivity of influenza virus and had a direct virucidal action. ORNs-d-M reduces influenza virus infectivity, affecting the HA-glycan interaction in vitro. By suppressing the influenza viral infection, the ORNs-d-M can have direct virucidal action.